2017
DOI: 10.17235/reed.2017.4947/2017
|View full text |Cite
|
Sign up to set email alerts
|

From the intestinal flora to the microbiome

Abstract: In this article, the history of the microbiota is reviewed and the related concepts of the microbiota, microbiome, metagenome, pathobiont, dysbiosis, holobiont, phylotype and enterotype are defined. The most precise and current knowledge about the microbiota is presented and the metabolic, nutritional and immunomodulatory functions are reviewed. Some gastrointestinal diseases whose pathogenesis is associated with the intestinal microbiota, including inflammatory bowel disease, irritable bowel syndrome and celi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 58 publications
(53 reference statements)
0
40
0
2
Order By: Relevance
“…Studies have confirmed that the occurrence of IBS can be linked to increased activation of the gut-brain axis, high visceral sensitivity, intestinal flora changes, and increased immune activation. It is worth noting that intestinal flora changes may vary between regions and these changes are primarily characterized by significant decreases in Bifidobacterium and Lactobacillus in Chinese patients and a decrease in Bifidobacteria and an increase in Bacteroides in European patients ( 26 , 27 ). Small intestine bacterial overgrowth (SIBO) is a condition characterized by the translocation of the distal intestinal flora to the small intestine in response to a variety of factors; this results in the overgrowth of anaerobic bacteria, which is responsible for the manifestation of a series of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the occurrence of IBS can be linked to increased activation of the gut-brain axis, high visceral sensitivity, intestinal flora changes, and increased immune activation. It is worth noting that intestinal flora changes may vary between regions and these changes are primarily characterized by significant decreases in Bifidobacterium and Lactobacillus in Chinese patients and a decrease in Bifidobacteria and an increase in Bacteroides in European patients ( 26 , 27 ). Small intestine bacterial overgrowth (SIBO) is a condition characterized by the translocation of the distal intestinal flora to the small intestine in response to a variety of factors; this results in the overgrowth of anaerobic bacteria, which is responsible for the manifestation of a series of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal flora is one of the most complex microbial systems in the human body. It is in a dynamic balance of symbiosis, coexistence, and co-prosperity between human hosts, and has a very important physiological function for human health (1,2). More and more studies have found that intestinal flora plays an important role in the occurrence of tumors, while digestive system tumors, as one of the most common malignant tumors in the world, also pose a serious threat to human health and constitute a major source of economic burden in the field of world public health (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Although the bacterial composition changes over 24 h, the enterotypes remain stable during a 10-day diet. 6,7,19,20 Benefits of probiotics, nutribiotics, and pharmabiotics There are six general mechanisms through which probiotics perform their beneficial effects, and there are essential differences between probiotic species and their strains. 3,7,12,13 Figure 2.…”
Section: Dysbiosis and Reinstatement Of Microbiotamentioning
confidence: 99%